Clinical Profile of Thoracoscopic Bullectomy in Treatment of Pneumothorax - Gautam, Pratima; Sapkota, Ranjan; Shrestha, Suraj; Mainali, Prakash (Journal of Nepal Health Research Council, 2024)
Background: In pneumothorax patients requiring surgery for various indications, thoracotomy was the traditional approach until the advent of video-assisted thoracoscopic surgery. In the last decade, role of thoracoscopy in the surgical management of pneumothorax has been consolidated and established. In this study, we aim to report our experience of thoracoscopy in the surgical management of pneumothorax.Methods: A descriptive review of prospectively maintained data on all the patients undergoing thoracoscopic bullectomy for pneumothorax was done.Result: Over the period of 9 years, a total of 120 patients underwent thoracoscopic bullectomy. Among them, 95 entered final analysis. Most common age group was 21-40 years, with male predominance (80%); most common diagnosis was primary pneumothorax (67%), first episode (74%), and on the right (65%) side; commonest symptom was shortness of breath (84%) of a median duration of 7 days. A chest tube was placed in 96% of patients before the operation. Commonest radiological finding was multiple bullae (45%) in the apical region (71%). Majority of patients underwent surgery via 3 ports, and a single bulla in the apical region was the most common intraoperative finding. Among the postoperative complications which occurred in 17%, an air leak was present in 9%. The median intensive care stay was 23 hours, the median chest tube duration was 3 days, and the median hospital stay was 9 days.Conclusions: Thoracoscopy can be used as a safe, feasible, and effective procedure in patients presenting with pneumothorax with minimal postoperative complications. Keywords: Bullectomy; pneumothorax; video-assisted thoracoscopic surgery.